Environmental Impact of Animal-Based Food Production and the Feasibility of a Shift Toward Sustainable Plant-Based Diets in the United States - Espinosa-Marrón, Alan; Adams, Kate; Sinno, Lea; Cantu-Aldana, Alejandra; Tamez, Martha; Marrero, Abrania; Bhupathiraju, Shilpa N.; Mattei, Josiemer (Frontiers in Sustainability, 2022)
Evidence consistently suggests that plant-based diets promote human and planetary health. Reducing large-scale animal-based food production generates environmental benefits, as the entire livestock agriculture chain plays an outsized role in greenhouse gas emissions, land change and degradation, and scarcity-weighted water use. However, substituting animal products with their plant-based counterparts must come with consideration of the nutritional quality and resource usage of plant-based food production and processing operations. Several policy reforms have been implemented at the national, state, and municipal levels in the United States to support a transition toward more plant-based diets. Federal programs such as the Supplemental Nutrition Assistance Program and the Dietary Guidelines for Americans generally promote the consumption of unprocessed plant-based foods but include little to no information on sustainability and the harmful environmental impact of animal-based foods. National policies are complemented by state efforts aimed at incentivizing produce purchased from local suppliers and encouraging resource-conserving agriculture. At the local level, public schools are implementing programs to promote plant-based protein on their menus, and urban gardens are sprouting across the country to increase access to organic farming. This mini-review examines these policy reforms and behavioral intervention strategies, based on the social-ecological model, and discuss their capacity and limitations to promote a shift toward sustainably produced plant-based diets in the United States. We conclude that transforming the food systems toward plant-based diets in the animal-centered United States requires multi-sector collaboration and context-specific policy solutions to address diet-related climate concerns without neglecting health, social, and financial constraints.